Pengembangan Game Simulasi Motorik untuk Anak Sekolah Dasar SDN 230 Palembang - Muammar Khadafi; Muhamad Ariandi (Jurnal Informatika Ekonomi Bisnis, 2025)
Games are popular technologies used for entertainment, and educational games combine play with learning to enhance concentration and thinking skills. This research addresses the lack of engaging learning media for first-grade students at SDN 230 Palembang and the prevalence of non-educational games. The study develops an educational game called Image Matching, aimed at teaching animal and fruit names while improving fine motor skills. The game, Animal Detective, is a puzzle game where students guess animal names based on pictures and descriptions. Using the System Development Life Cycle method, including planning, analysis, design, development, and testing with the Black Box method, this game serves as an interactive learning media. Results show that it effectively improves motor skills and knowledge about animals and fruits. The game is expected to provide engaging education and entertainment for first-grade students at SDN 230 Palembang.